Research on security defense of mobile edge computing - Lu CHEN; Hongbo TANG; Wei YOU; Yi BAI (网络与信息安全学报)
Mobile Edge Computing can solve the problem of heavy backhaul link overloaded and long delay effectively by further extending the telecommunication cellular network to other wireless access networks.However， the MEC nodes are exposed to the edge of the network whose computing resource, storage capacity and energy resource are limited, they are more vulnerable to the illegal attacks by attackers.Based on the briefly analysis of the security threats faced by mobile edge computing, some key problems and challenges of mobile edge computing for four different security subjects, device security, node security, network resources and tasks, and migration security are summed up and expounded, and the existing security solutions were summarized.Finally, the open research and future development trend of mobile edge computing security defense on three aspects that limited resource defense model in the dynamic scene, resource deployment based on comprehensive trust and user-centered service reliability assurance are discussed.